The relations between the Jewish Bund and the RSDRP, 1897-1903 - Shukman, H; Shukman, H. (1961)
The Jewish Social Democrats who founded the Bund in 1897 were russified intellectuals who saw the Jewish labour movement as an integral part of the Russian revolutionary movement. Thanks to the greater deprivations and higher revolutionary potential of the Jewish workers, the Jewish Social Democrats made contact with the masses earlier than their Russian counterparts. The turn to mass agitation for economic demands as a means of awakening the political consciousness of the masses was given theoretical justification by a leading Vilna Social Democrat, Arkadi Kremer, in Ob Agitatsii (1894) By the mid-nineties a politically led labour movement, centred on Vilna, had developed in the north-west region of the Jewish Pale of Settlement, The leaders of this movement were closely associated with the Social Democrats of St. Petersburg and those in exile abroad. From the mid-nineties, the Vilna Social Democrats made deliberate efforts to spread their experience to other cities in Russia. The founding of the Bund in September 1897 was a formalization of the existing labour organization. It was hastened by the imminent prospect of the formation of the ail-Russian Social Democratic Party and by the activities of Arkadi Kremer. Kremer, by his contacts with Social Democrats in Petersburg and Kiev, and with the Plekhanov Group abroad, was also partly instrumental in summoning the First Congress of the RSDRP held in March 1898. The main initiative for this, however, belongs to the Kiev Social Democrats. The Congress was held in Minsk, the seat of the Bund's Central Committee who were responsible for the technical arrangements for the Congress. Kremer became one of the three members of the new Party's Central Committee, and through his association with Plekhanov arranged that the new Party should be represented abroad by the Union of Russian Social Democrats. The Congress unanimously agreed to the Bund's request for autonomy in all matters pertaining to the Jewish proletariat. [continued in text ...]